Utilization of E-money for School Payments Using Web-Based RFID Sensors - Rakasiwi, Sindhu; Kusumo, Haryo (Universitas PGRI Semarang, 2021)
School payments are a very important issue to support a school that is used to meet infrastructure and other needs. Therefore, if there is an error in writing or the loss of payment data, a difficult problem will arise. Because the payment process is still manual using a notebook.By utilizing E-money and RFID Sensors in the school payment process, it will be very helpful to create an effective and efficient payment process. That is by using school student cards as self-identity in searching for data that will be linked to a web as a basis. In paying school fees, you can also use E-money for the payment process. Therefore, the author will use electronic money to process the payment. That is by utilizing server-based electronic money in the form of applications such as OVO and DANA. Because it is easier and has been registered with Bank Indonesia, it will be guaranteed safe. The way it works is the first by installing an RFID sensor on the student card which functions as a means of finding personal data or identity so there is no need to search for data one by one manually. Furthermore, it will be linked to the website as a payment basis, where when the RFID sensor is successful in scanning student data, a payment option will appear, which can be paid directly or through the available OVO and DANA electronic money.